Trajetórias escolares de estudantes da UFSCar dos cursos de pedagogia presencial e a distância : contribuição ao estudo da formação docente - Pereira, Mônica (Universidade Federal de São Carlos, 2016)
This work chooses as object of study the life and school trajectories of a student group of formal Pedagogy course (daytime and evening courses - campus of São Carlos) and Pedagogy distance course, at the Federal University of São Carlos (UFSCar). The research has a descriptive and analytical nature and is based, as main theoretical analysis, on the studies of Pierre Bourdieu (1975; 1983; 1994; 1998a; 1998b; 2002; 2005; 2008; 2009), especially the notion of habitus, cultural capital, economic capital and social capital. The hypothesis is that students enrolled in the Faculty of Pedagogy in different modalities (formal and distance education) have different profiles and school trajectories. Thus, it is important to describe its trajectories, identifying how related they are, if similar or different, so that it is possible to understand the contents of each path in the light of certification specificity to which the Pedagogy course corresponds. The research’s basic procedure is to collect documentary data sources as: Pedagogical Project of the course in each modality, course’s legislation and bibliographical research on the theme. The first step in collecting the information for the profile of the students took place through a questionnaire with content involving socioeconomic aspects, family, professional, educational and cultural. 184 students (39, daytime course; 42, evening, 103, online) have participated in this first stage of the research. The second stage of the data collection was carried out through semistructured interviews on which 18 students (6, daytime course; 6, evening; 6, online) have participated. This study was based on content analysis (Bardin, 1977), and the organization of the data gathered aimed to present a quantitative and detailed description of the information obtained from encodings that had as a unity sense the school trajectories of the participating students. The search results provide information on teacher training and professional performance expectation of students, data that allow to reflect on the very configuration of the Pedagogy course in the two modalities. Regarding the school trajectories of students, it was observed that 71% of the investigated group underwent primary and secondary education in public schools. An important data in relation to the students enrolled in distance education programme is that 63% of this group have already completed other graduation course. A possible comparison between the group trajectories allowed to understand how social practices, economic practices, professional practices and cultural background from the family can interfere in school trajectories of students and, consequently, in the decision-making process for choosing Higher education.
Keywords: Trajetórias escolares; Curso superior; Estudantes de pedagogia; Formação docente; Capital cultural; School trajectories; Higher education; Pedagogy students; Educational formation; Habitus; CIENCIAS HUMANAS::EDUCACAO